You are on page 1of 4

Prove: (p∧¬q) ∨ q ⇔ p∨q

(p∧¬q) ∨ q Left-Hand Statement


Proofs Using Logical ⇔ q ∨ (p∧¬q) Commutative
Equivalences ⇔ (q∨p) ∧ (q ∨¬q) Distributive
⇔ (q∨p) ∧ T Negation
Rosen (6th Ed.) 1.2 ⇔ q∨p Identity
⇔ p∨q Commutative
Note: These are all Direct Proofs
Begin with exactly the left-hand side statement
End with exactly what is on the right
Justify EVERY step with a logical equivalence

Prove: (p∧¬q) ∨ q ⇔ p∨q Prove: p → q ⇔ ¬q → ¬p


(p∧¬q) ∨ q Left-Hand Statement Contrapositive
p→q
⇔ q ∨ (p∧¬q) Commutative
⇔ ¬p ∨ q Implication Equivalence
⇔ (q∨p) ∧ (q ∨¬q) Distributive
⇔ q ∨ ¬p Commutative
Why did we need this step?
⇔ ¬(¬q) ∨ ¬p Double Negation
Our logical equivalence specified that ∨ is distributive on the
right. This does not guarantee distribution on the left! ⇔ ¬q → ¬p Implication Equivalence
Ex.: Matrix multiplication
(Note that whether or not ∨ is distributive on the left is not the
point here.)

Prove: p → p ∨ q is a tautology Why do I have to justify


Must show that the statement is true for any value of p and q.
everything?
p→p∨q •  Note that your operation must have the
⇔ ¬p ∨ (p ∨ q) Implication Equivalence same order of operands as the rule you
⇔ (¬p ∨ p) ∨ q Associative quote unless you have already proven (and
⇔ (p ∨ ¬p) ∨ q Commutative cite the proof) that order is not important.
⇔ T∨q Negation
•  3+4 = 4+3
⇔ q∨T Commutative
•  3/4 ≠ 4/3
⇔ T Domination
A*B ≠ B*A for everything!
This tautology is called the addition rule of inference.

1
Prove: (p∧q) → p is a tautology Prove or Disprove
p → q ⇔ p ∧ ¬q ???
(p∧q) → p
⇔ ¬(p∧q) ∨ p Implication Equivalence
To prove that something is not true it is
⇔ (¬p∨¬q) ∨ p DeMorgan’s
enough to provide one counter-example.
(Something that is true must be true in every
⇔ (¬q∨¬p) ∨ p Commutative
case.)
⇔ ¬q∨ (¬p ∨ p) Associative
⇔ ¬q∨ (p ∨ ¬p) Commutative
p q p→q p∧¬q
⇔ ¬q∨ T Negation FT T F
⇔ T Domination The statements are not logically equivalent

Class Exercise: Without using truth tables,


prove that ((p∨q)∧¬p)→q is a tautology.
Prove:¬p ↔ q ⇔p ↔ ¬q p∧T ⇔ p; p∨F ⇔ p Identity Laws
p∨T ⇔ T; p∧F ⇔ F Domination Laws
p∨p ⇔ p; p∧p ⇔ p Idempotent Laws
¬p ↔ q ¬(¬p) ⇔ p Double Negation Law
p∨q ⇔ q∨p; p∧q ⇔ q∧p Commutative Laws
⇔ (¬p→q) ∧ (q→¬p) Biconditional Equivalence (p∨q)∨ r ⇔ p∨ (q∨r); (p∧q) ∧ r ⇔ p ∧ (q∧r) Associative Laws
⇔ (¬¬p∨q) ∧ (¬q∨¬p) Implication Equivalence (x2) p∨(q∧r) ⇔ (p∨q)∧(p∨r) Distributive Laws
p∧(q∨r) ⇔ (p∧q)∨(p∧r)
⇔ (p∨q) ∧ (¬q∨¬p) Double Negation ¬(p∨q)⇔(¬p ∧ ¬q) De Morgan’s Laws
⇔ (q∨p) ∧ (¬p∨¬q) Commutative ¬(p∧q)⇔(¬p ∨ ¬q)
p ∨ (p∧q) ⇔ p Absorption Laws
⇔ (¬¬q∨p) ∧ (¬p∨¬q) Double Negation p ∧ (p∨q) ⇔ p
⇔ (¬q→p) ∧ (p→¬q) Implication Equivalence (x2) p ∨ ¬p ⇔ T Negation Laws
p ∧ ¬p ⇔ F
⇔ p ↔ ¬q Biconditional Equivalence (p→q) ⇔ (¬p ∨ q) Implication Equivalence

Class Exercise: Without using truth tables,


prove that ((p∨q)∧¬p)→q is a tautology.
((p∨q)∧¬p)→q
¬((p∨q)∧¬p) ∨ q Implication Equivalence

Normal or Canonical Forms
⇔ (¬(p∨q) ∨ ¬¬p) ∨ q DeMorgan
⇔ (¬(p∨q) ∨ p) ∨ q Double Negation
⇔ ¬(p∨q) ∨ (p∨q) Associative Rosen (6th Ed.) 1.2 (exercises)
⇔ (p∨q) ∨ ¬(p∨q) Commutative
⇔ T Negation

2
Logical Operators Functionally Complete
∨ - Disjunction Do we need all these? •  A set of logical operators is called
∧ - Conjunction functionally complete if every compound
¬ - Negation proposition is logically equivalent to a
→ - Implication p→q = ¬p ∨ q compound proposition involving only these
⊕ - Exclusive or (p ∧ ¬q) ∨ (¬p ∧ q) logical operators.
↔ - Biconditional p↔q⇔ •  ∧, ∨, and ¬ form a functionally complete
(p→q) ∧ (q→p) ⇔ set of operators.
(¬p ∨ q) ∧ (¬q ∨ p)

Are ¬(p∨(¬p∧q))
Are ¬(p∨(¬p∧q))
and (¬p ∧ ¬q) equivalent?
¬(p∨(¬p∧q))
and (¬p ∧ ¬q) equivalent?
⇔  ¬p ∧ ¬(¬p∧q) DeMorgan •  Even though both are expressed with only
⇔ ¬p ∧ (¬¬p∨¬q) DeMorgan ∧, ∨, and ¬, it is still hard to tell without
⇔ ¬p ∧ (p∨¬q) Double Negation doing a proof.
⇔ (¬p∧p)∨(¬p ∧¬q) Distribution •  What we need is a unique representation of
⇔ (p∧¬p)∨(¬p ∧¬q) Commutative a compound proposition that uses ∧, ∨, and
⇔ F ∨(¬p ∧¬q) Negation ¬.
⇔  (¬p ∧¬q) ∨ F Commutative
•  This unique representation is called the
⇔  (¬p ∧¬q) Identity
Disjunctive Normal Form.

Disjunctive Normal Form Truth Table


•  A disjunction of conjunctions where every p q p⊕q (p∧¬q) ∨ (¬p∧q)
variable or its negation is represented once T T F F
in each conjunction (a minterm) T F T T
–  each minterm appears only once
F T T T
Example: DNF of p⊕q is
F F F F
(p∧¬q)∨(¬p∧q).

3
How to find the DNF of (p ∨ q)→¬r
Method to construct DNF p q r (p ∨ q)
¬r (p ∨ q)→¬r
•  Construct a truth table for the proposition. T T T T F F
T T F T T T
•  Use the rows of the truth table where the
T F T T F F
proposition is True to construct minterms T F F T T T
–  If a variable is false, use the negation of the F T T T F F
variable in the minterm F T F T T T
–  If the variable is true, use the propositional F F T F F T
variable in the minterm F F F F T T
•  Connect the minterms with ∨’s. There are five sets of input that make the statement
true. Therefore there are five minterms.

p q r (p ∨ q)
¬r (p ∨ q)→¬r
T T T T F F
Can we show that just ¬ and ∧ form a set
T T F T T T of functionally complete operands?
T F T T F F
Use DeMorgan’s Laws on the DNF.
T F F T T T
Example:
F T T T F F
(p ∨ q)→¬r
F T F T T T
⇔ (p∧q∧¬r) ∨ (p∧¬q∧¬r) ∨ (¬p∧q∧¬r) ∨
F F T F F T (¬p∧¬q∧r) ∨ (¬p∧¬q∧¬r) DNF
F F F F T T ⇔ ¬ ¬[ (p∧q∧¬r) ∨ (p∧¬q∧¬r) ∨ (¬p∧q∧¬r) ∨
From the truth table we can set up the DNF (¬p∧¬q∧r) ∨ (¬p∧¬q∧¬r)] Double Neg
(p ∨ q)→¬r ⇔ (p∧q∧¬r) ∨ (p∧¬q∧¬r) ∨ ⇔ ¬[¬(p∧q∧¬r) ∧ ¬(p∧¬q∧¬r) ∧ ¬(¬p∧q∧¬r) ∧
(¬p∧q∧¬r) ∨ (¬p∧¬q∧r) ∨ (¬p∧¬q∧¬r) ¬(¬p∧¬q∧r) ∧ ¬(¬p∧¬q∧¬r)] DeMorgan

Find an expression equivalent to p → q Now can we write an equivalent statement to p → q


that uses only conjunctions and negations. that uses only disjunctions and negations?
p q p→q
How many minterms in p→q
T T T the DNF? ⇔ ¬[¬(p∧q) ∧ ¬(¬p∧ q) ∧ ¬(¬p∧ ¬q)] From Before
T F F ⇔ ¬[(¬p∨¬q) ∧ (¬¬p∨¬q) ∧ (¬¬p ∨ ¬¬q)] DeMorgan
F T T ⇔ ¬[(¬p∨¬q) ∧ (p∨¬q) ∧ (p∨q)] Doub. Neg.
⇔ ¬(¬p∨¬q) ∨ ¬(p∨¬q) ∨ ¬(p∨q) DeMorgan
F F T
The DNF of p → q is (p∧q) ∨ (¬p∧ q) ∨ (¬p∧ ¬q).
Then, applying DeMorgan’s Law, we get that this is
equivalent to
¬[¬(p∧q) ∧ ¬(¬p∧ q) ∧ ¬(¬p∧ ¬q)].

You might also like